Perspectives of employers on graduate employability skills: A case of Malaysia - Yuan, Yee Yen; Wendy Teoh, Ming Yen; Chong, Siong Choy; Tee, Win Nee; Teoh, Ming-Li (AESS Publications., 2023)
One of the main reasons for the low employment rate of Malaysian graduates is a lack of skills. A substantial number of employers have expressed dissatisfaction with the quality of graduates, claiming that they lack the necessary skills required for successful employment. This research aims to investigate the perceptions of employers on the importance and level of satisfaction with the employability skills of graduates and subsequently examine the gap between them (level of importance and satisfaction). The survey included 63 employers from the manufacturing industry, and the data were analyzed. The results suggest that employers viewed all eight skills, such as English communication skills, thinking skills, positive attitude and teamwork, work planning skills, work discipline, self-motivation, and technology skills, as essential employability skills. However, the gap analysis reveals that they were dissatisfied with the skills possessed by the graduates, indicating that the skills of the graduates fell short of their expectations, which is consistent with their dissatisfaction. The highest differences between satisfaction and expectation arise from English communication skills and thinking skills, followed by self-motivation, a positive attitude, teamwork, work planning skills, technology skills, and work discipline skills. This study provides important insights for graduates, higher education institutions, and policymakers in Malaysia, as well as in countries facing the issue of the low employability of graduates.